Diagnostic Accuracy of Emergency Ultrasonography Compression by Non-Radiologists or Cardiologists for Diagnosis of Deep Vein Thrombosis in Lower Extremity: An Evidence-Based Case Report - Ayers Gilberth Ivano Kalaij; Mohamad Syahrir Azizi; Angga Pramudita (Interna Publishing, 2023)
Background: Deep vein thrombosis (DVT) is a medical condition with dangerous complications including lung thromboembolism which can cause death. However, the disease is often neglected, leading to delays in diagnosis and treatment. Patients with lower extremity DVT clinical signs and symptoms usually cause diagnostic dilemmas, specifically for general practitioners (GP). Various diagnostic strategies have been proposed to diagnose DVT although they still have several limitations. Therefore, emergency compression US by non-radiologists or cardiologists needs to be further considered as a fast and accurate alternative. This study aimed to analyze the potency emergency compression US by non-radiologists or cardiologists to diagnose DVT in the lower extremity. Methods: A comprehensive literature search was conducted through PubMed, Scopus, and Cochrane Library. The articles were screened based on predetermined inclusion and exclusion criteria with the keywords emergency, general practitioners, compression US, and DVT. Critical appraisal was performed using the Oxford CEEBM Critical Appraisal Tools for Diagnostic studies criteria. Results: This study analyzed a total of five cross-sectional studies and one prospective cohort. The emergency compression US performed by general practitioners and emergency physicians had a sensitivity of 86-93% and specificity of 90-97.1%. This analysis produced reliable results for diagnosing DVT in bedside settings compared to compression or doppler US performed by experts. Conclusion: Emergency compression US performed by general practitioners and emergency physicians had great potential to be a fast and accurate method for diagnosing and excluding DVT in lower extremities. However, standardized training is necessary to produce the highest diagnostic accuracy.